2015
DOI: 10.1007/s00402-015-2225-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser engravings as reason for mechanical failure of titanium-alloyed total hip stems

Abstract: Laser engravings need to be reduced to a minimum of necessary information, and should be placed at locations with minimum mechanical load. Biomechanical analyses are recommended to identify less loaded areas in implant components to avoid such implant failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…We note that durability of femoral prostheses was studied in [ 23 ] on 95 patients with osteonecrosis, without developing a mathematical model. Mallory showed [ 24 ] that the femoral component geometry influences the durability of a prosthesis, while in [ 25 ] it was shown that even engravings may be the reason for mechanical failure of a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We note that durability of femoral prostheses was studied in [ 23 ] on 95 patients with osteonecrosis, without developing a mathematical model. Mallory showed [ 24 ] that the femoral component geometry influences the durability of a prosthesis, while in [ 25 ] it was shown that even engravings may be the reason for mechanical failure of a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ablative laser marking (laser engraving) has been used to provide traceability to hip-implants by the engraving of a serial number. This has been shown to be a preferred crack initiation site in titanium, presumably due to the stress concentration of what is effectively a notch [11,12]. In addition, dissolution of appreciable amounts of oxygen has been identified in the surface-near region after engraving, which potentially contributes to embrittlement.…”
Section: Introductionmentioning
confidence: 99%